Integrative Analysis of Androgen Receptor Interactors Aberrations and Associated Prognostic Significance in Prostate Cancer - Wang, Zhu; Zhang, Ying; Deng, Qiong; Zhang, Jianwen; Wang, Xisheng; Liang, Hui (Urology Journal, 2023)
Purpose: Much progress has been made by directing against the adrogen receptor (AR) pathway in the treatment of prostate cancer in past decades. However, AR-interactors related metastatic castration resistant prostate cancer eventually developed. Here, we aimed to characterize the aberrations and therapeutic implication in advanced disease. Materials and Methods: STRING database, UALCAN web portal and cBioPortal platform was used to analyze the AR interaction network, gene alterations, as well as the prognostic significance. GO and KEEG analysis was performed to characterize the functional enrichment of the identified AR-interactors. Results: Ten first shell AR-interactors were identified, among of which FOXA1 and PELP1 was significantly up-regulated, while CCND1, CTNNB1, NCOA4 and HSP90AA1 exhibited a significantly decreased pattern. The median survival period of altered group (n = 227) was 70 months (95% CI, 60-105M), while that of non-altered group (n = 545) was 141 months (95% CI, 115.13-NA, P < 0.001). GO and KEGG enrichment showed that the identified AR-interactors were particularly enriched in prostate cancer and thyroid hormone signaling pathway, as well as endocrine resistance. Conclusion: The AR-interactors might be useful markers for prostate cancer diagnosis and prognosis, and provide a new sight for revealing the molecular mechanism of CRPC progression.